2018
DOI: 10.20524/aog.2018.0266
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus reactivation in HBsAg-negative, anti-HBc-positive patients receiving immunosuppressive therapy: a systematic review

Abstract: Background:The optimal management of HBsAg-negative, anti-HBc-positive patients who receive immunosuppression remains unclarified. We systematically reviewed the available data on potential predictors of the risk of hepatitis B virus (HBV) reactivation in such patients.Methods:A literature search identified 55 studies with 3640 HBsAg-negative, anti-HBc-positive patients who received immunosuppressive regimens.Results:HBV reactivation was reported in 236 (6.5%) patients. The pooled HBV reactivation rates did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 65 publications
0
64
0
Order By: Relevance
“…A HBV reactivation rate of 6.5% during immunosuppressive treatment was reported, and the rate was higher in cases with hematological disorders or under rituximab treatment. 9 HBsAg-positive patients showed a higher rate of HBV reactivation than HBsAg-negative patients. 26 It has also been reported that negative or low HBsAb titer, immunosuppressive treatment duration of more than 1 year, combined immunosuppressants, advanced age and high-dose corticosteroids even for short courses can be risk factors for HBV reactivation.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…A HBV reactivation rate of 6.5% during immunosuppressive treatment was reported, and the rate was higher in cases with hematological disorders or under rituximab treatment. 9 HBsAg-positive patients showed a higher rate of HBV reactivation than HBsAg-negative patients. 26 It has also been reported that negative or low HBsAb titer, immunosuppressive treatment duration of more than 1 year, combined immunosuppressants, advanced age and high-dose corticosteroids even for short courses can be risk factors for HBV reactivation.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, serum HBV DNA turned positive during systemic corticosteroid treatment in 3.4% of cases. A HBV reactivation rate of 6.5% during immunosuppressive treatment was reported, and the rate was higher in cases with hematological disorders or under rituximab treatment . HBsAg‐positive patients showed a higher rate of HBV reactivation than HBsAg‐negative patients .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations